(untitled) (American Journal of Islam and Society, 2013)
Amr Abdalla (professor and vice rector, University for Peace, San Jose, Costa Rica) visited the International Institute of Islamic Thought (IIIT) on February 1, 2013, to discuss the challenges of conflict resolution and peace that has caught the attention of so many Muslim and non-Muslim scholars and policymakers for several decades. As the Muslim world remains plagued with violent confrontations between states and non-state actors, regional and national sectarian conflicts, and domestic conflicts with gender and family elements, such a discussion is very timely. The outbreak of the Arab Spring, which has resulted in several Islamist groups taking power, has raised various questions: Why is it important to talk about conflict resolution and peace building in an Islamic context? How can the theoretical be combined with the practical? How does Islam fit into the demonstrations that occurred during the Arab Spring as well as into modernity? This is, according to Abdalla, the first opportunity that contemporary Muslims have had to answer these questions for themselves ...